Effects of growth hormone transgene expression and triploidy on acute stress indicators in Atlantic salmon (Salmo salar L.) - Cnaani, Avner; McLean, Ewen; Hallerman, Eric M. (Aquaculture, 2013)
Transgenic Atlantic salmon (Salmo salar) expressing an opAFP-csGH transgene exhibit 3–6-fold growth rate acceleration in the first years of life. Transgenics intended for production likely will be triploids for purposes of reproductive confinement. Growth hormone (GH) transgene expression and triploidy may affect physiological traits with bearing on fitness, animal welfare, and aquaculture production. The goal of our study was to determine the responses of juvenile GH-transgenic and triploid Atlantic salmon to stress. Groups of one-year old conventionally bred (termed wild-type), GH-transgenic, and triploid Atlantic salmon were subjected to no stress (control), one-week of fasting, or low dissolved oxygen (1.5–2.0ppm) in triplicated tanks. Blood samples were taken from anesthetized fish, and nine markers of primary and secondary stress response were quantified. In addition, these stress-response markers were monitored over a time-course of 0, 1, 3, 6, and 24h after handling and air exposure stress. For fish subject to no stress, parameters measured did not differ among genotypes, except that blood pH was higher and pO2 and potassium levels lower in wild-type than in triploid or transgenic salmon. Immediately after one week of fasting, transgenic fish exhibited higher levels of sodium and chloride than other genotypes, suggesting osmoregulatory difficulty. Immediately after anoxic challenge, transgenic fish exhibited higher hematocrit, pCO2, glucose and sodium levels than other genotypes. In the time-course study, levels of stress-response indicators tended to peak at higher levels in GH-transgenic than in triploid than in wild-type salmon, and to not return to baseline levels through 24h. Results of the experiments collectively demonstrated that wild-type fish maintained homeostasis more effectively than transgenic or triploid fish, exhibiting smaller changes in all measured stress-response parameters. Poor stress response may affect aquaculture performance of transgenic or triploid Atlantic salmon and hence the aquaculture practices needed for their production and maintenance of welfare, and also may reduce their fitness in the wild. •We subjected GH-transgenic and triploid Atlantic salmon to fasting and anoxia.•After 1-week fast, transgenic fish exhibited higher Na+ and Cl− than other genotypes.•After anoxia, transgenic fish had higher hematocrit, pCO2, glucose and sodium.•Wild-type maintained homeostasis more effectively than transgenic or triploid fish.•Poor stress response may affect culture of transgenic or triploid Atlantic salmon.